Deserción estudiantil y limitada orientación vocacional en la carrera de Ingeniería en Gestión Empresarial de la Universidad Técnica Estatal de Quevedo, desde el periodo lectivo 2004-2005 hasta 2008-2009 - Baque Villanueva, Lisenia Karina (2010)
The present titled investigation: "DESERTION STUDENT AND LIMITED VOCATIONAL ORIENTATION IN THE CAREER OF THE EMPRESARIAL GESTION ENGINERY OF THE STATE TECHNICAL UNIVERSITY DE QUEVEDO, SINCE THE LECTIVE YEARS 2004-2005 UNTIL 2008 - 2009", it arises like a necessity to largely face the problem of Student Desertion of the Career of Empresarial Gestion Enginery, of the Empresarial Sciences Faculty, the limited and scarce Vocational Orientation that doesn't guarantee a correct election of the career to continue and for wherever the permanency in the studies until achieving their professional title. In a second point, it can show that the student desertion of the Career of the Empresarial Gestion Enginery, of the Empresarial Sciences Faculty, is due to the lack of economic resources that has most of the Ecuadorian families and quevedeñas, reason for the one which the students interrupt their university studies for the necessity of generating economic revenues for their families. For these facts, it is yearned: • That the Authorities and Directive of the Empresarial Sciences Faculty design and implement the Department of Vocational and Professional Orientation, for the help of the students in general. • That in the educational process the execution of tasks is looked for that don't imply bigger economic investment that the family economy can shrink and this way, to avoid the desertion. The most important strategies analyzed in the present investigation are: • Atend the students like individuals that belong to an institutional student group. • Considerate to the student like an active entity, so that it participates in the taking of professional decisions on the base of a complete process of reflection of the possibilities that he/she offers him the means in that it is developed for the study of an or another profession. The benefits that are hoped to obtain in this investigation respond to: • To lower the levels of student desertion. • That in the orientation to the students all the educational agents participate: authorities, directive, educational, psychologists, educators, family parents, etc. • To brindate the necessary support to the students for potenciate a future vision that guarantees them professional successes.